Aplication ADeV Aplikasi Air Detection Environment System (ADeV) Dalam Mendeteksi Kadar Kualitas Udara Di Area Parkiran Berbasis Android - Ade Silvia Handayani; Al Fatur Sayid; Sopian Soim; Nyayu Latifah Husni; Rumiasih Rumiasih; Rosmalinda Permatasari (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2020)
This paper presents an application of Air Detection Environment System using Android that based on the WSN technology. This technology related to multiple sensors that could detect the air quality of environmental parking lot. The proposed application has been successful in detecting automatically the air quality of vehicle exhaust, such as CO, CO2, HC, PM10, temperature, and humidity. This multisensors technology can trasmit air quality data to servers and displays some menu, such as: the air quality status, the time, and the location of the event. This application will be benefit for the people to know the surround environmental condition practically, in real time and in mobile. It is due to they only need to have access to their smart application. It is expected that they will increase their safety and attention of to the unhealthy environmental qualities.